Myasthenia gravis with thymoma and autoimmune haemolytic anaemia. A case report - TANRIDAĞ, TÜLİN (SPRINGER-VERLAG, 2003)
Myasthenia gravis is an autoimmune disorder that affects the neuromuscular junction and leads to weakness of the skeletal muscles. Associated autoimmune diseases such as systemic lupus erythematosus, rheumatoid arthritis and pernicious anaemia are present in approximately 5% of the myasthenic patients. This report presents a 64-year-old man with autoimmune haemolytic anemia associated with myasthenia gravis and thymoma. The patient developed a severe Coomb's positive autoimmune haemolytic anaemia, which was resistant to treatment with large doses of prednisone. Haemolytic anaemia entered remission one month following thymectomy, and the patient has maintained a normal haemoglobin and a negative Coomb's test without the need for steroid or immunosuppressive therapy. In conclusion, thymectomy may induce a striking improvement of therapy-resistant autoimmune haemolytic anemia in patients with MG and thymoma, but in terms of remission, a long follow-up is needed as autoimmune diseases can show spontaneous fluctuations.
Keywords: autoimmune haemolytic anemia; myasthenia gravis; thymoma; HEMOLYTIC-ANEMIA; CELL APLASIA